QUALITY OF JAPANESE QUAIL (Coturnix-coturnix japonica) EGGS WITH DRAGON FRUIT PEEL JUICE ON DRINKING WATER - I K. Y., Sujana; Dewi, G. A. M. K.; Wirapartha, M. (Jurnal Peternakan Tropika; Vol 9 No 3 (2021): Vol. 9 No. 3 Tahun 2021; September - December, 2021)
This study aims to determine the egg quality of Japanese quail ( Coturnix-coturnix japonica ) given dragon fruit peel juice in drinking water.  The design used was Completely Randomized Design (CRD) with four (4) treatments and four (4) replications, each replication consisted of 5 quails aged 6-10 weeks.  The four treatments were: P0: drinking water without dragon fruit peel juice or control, P1: drinking water given dragon fruit peel juice as much as 1%, P2: drinking water given dragon fruit peel juice as much as 2%, P3: drinking water given dragon fruit skin juice as much as 3%.  The variables observed were egg weight, egg shell weight, egg shell thickness, egg white weight, egg yolk weight, egg yolk color, HU ( Haugh Unit ), egg pH. The results obtained from the treatment of  P0 drinking water without dragon fruit peel juice, P1 (1% dragon fruit peel juice on drinking water), P2 (2% dragon fruit peel juice on drinking water), P3 (3% dragon fruit peel juice on drinking water).  That showed eggs quality such as: egg weight, egg shell eight, egg shell thickness, egg white weight, egg yolk weight, egg yolk color, HU ( Haugh Unit ) and pH were not statistically significant (P>0,05) between treatments.  The conclusion of this study is giving gragon fruit peel juice 0%, 1%, 2%, and 3% through drinking water had the same value on in japanese quail ( Coturnix-coturnix japonica ) eggs. Keywords : egg weight, egg yolk color, HU (Haugh Unit), egg pH